Regional myocardial function in children with chronic aortic regurgitation - Goebel, Björn Carsten; Poerner, Tudor; Gorenflo, Matthias; Lauten, Alexander; Jung, Christian; Grohmann, Jochen; Figulla, Hans; Arnold, Raoul (Echocardiography, 2010)
AIM: To determine the influence of volume overload on regional myocardial function in children with aortic regurgitation (AR) using tissue Doppler echocardiography and strain rate imaging (TDE/SRI). - METHODS: Thirty children with AR (median age 14 years (range 3-28 years)) were divided into three groups: mild (n = 6), moderate (n = 15), and severe AR (n = 9). Patients and 30 matched healthy controls underwent echocardiography with TDE/SRI. Cineloops were acquired from parasternal long- and short-axis and from apical four- and two-chamber views. The following parameters were extracted: peak systolic (V(S) ) and diastolic (V(E) ) velocities, peak systolic strain (S), peak systolic (SR(S) ), and early diastolic strain rate (SR(E) ). To quantify longitudinal LV function, V(S) and V(E) were obtained as peak values in the basal segments, whereas S, SR(S) , and SR(E) were expressed as mean values between basal and midwall segments. - RESULTS: Compared to the control group, patients showed a significant reduction in V(E) in the longitudinal direction (-91 ± 30 mm/sec for patients vs. 119 ± 20 mm/sec for control group). In patients with severe AR, longitudinal SR(E) was significantly reduced. On the other hand, we noted no differences between patients and controls with regard to S and SR(S) values. - CONCLUSION: Children with AR presented with significantly reduced longitudinal diastolic function (V(E) ). Severe AR leads to a decrease in diastolic myocardial deformation (SR(E) ). Due to the short duration of AR in this group of patients, systolic function (SR(S) ) is still preserved.